SYNTHESIS OF NEW N-HYDROXYPHENYL AND TOLYL DERIVATIVES OF PYRIMIDINE-4(1H) –ONE WITH ANTI-INFLAMMATORY ACTIVITY - I. P. Kodonidi; O. O. Novikov; S. A. Kuleshova; Ju. I. Rjabukhin; S. S. Shatokhin; A. V. Ivchenko; M. I. Kodonidi; O. M. Zhilina (Фармация и фармакология (Пятигорск), 2018)
In their structure pyrimidin-4-one derivatives are similar to the endogenous nitrogen bases. This makes it possible to predict a wide range of pharmacological activities characteristic for them. The compounds of this series exhibit neurotropic, immunotropic, actoprotective, hypotensive, antihypoxic, anti-infl ammatory and antioxidant activity. Within this framework, the search for and creation of highly effective and safe anti-infl ammatory drugs in the series of N-arylpyrimidin-4(1H)-one is of great current interest.The aim of the work is to carry out predictive studies and targeted synthesis of N-substituted derivatives of pyrimidine-4(1H)-one with anti-infl ammatory activity, as well as toconfi rm the validity of their molecular construction by the results of pharmacological tests.Materials and methods. The research was carried out using the logical-structural approach and information technologies. The computer analysis of biological activity was carried out by the PASS program. Synthesis of the target compounds was carried out using a modifi ed procedure. The structure of the synthesized compounds was confi rmed by 1H NMR, IR and UV spectroscopy. The investigation of the anti-infl ammatory effect of the synthesized compounds was carried out on the model of acute aseptic infl ammation. The synthesized substances were injected intraperitoneally, the magnitude of the edema was the criterion for evaluating the anti-infl ammatory activity.Results and discussion. In the course of the research on the basis of the logico-structural approach, hydroxyphenyl and alkyl derivatives of pyrimidin-4(1H)-one with anti-infl ammatory properties were validated. A preliminary analysis of the pharmacological properties of the predicted structures was carried out using the PASS program and the most promising compounds were selected. To synthesize the tolyl and hydroxyphenyl derivatives of pyrimidin-4(1H)-one, a modifi ed procedure was used. Its essence consists in the use of catalytic amounts of dimethylsulfoxide in order to increase the nucleophilicity of the amine component of the reaction. In order to confi rm the reliability and expediency of the molecular construction, the antiexudative activity of the target compounds was studied.Conclusion. The results of pharmacological studies indicate the prospect of searching for and creating new biologically active compounds having anti-infl ammatory activity among the tolyl and hydroxyphenyl derivatives of pyrimidin-4(1H)-one.